Pelatihan Perencanaan Keuangan pada Bisnis Baru di Rumah Hasanah Margahayu, Bandung - Hasanah, Yulia Nur; Rizaldi, Fikri Mohamad; Prasetiyo, Budi (LPPM Universitas Bina Sarana Informatika, 2024)
Financial Planning Training for New Businesses plays a crucial role in addressing the challenges faced by new business owners, particularly in managing finances. The main problem often encountered is the lack of knowledge and experience in business financial management. This training aims to provide a deep understanding of the process of building a new business while designing efficient financial planning. The implementation method includes the dissemination of basic financial planning concepts, cash flow preparation practices, and simple financial statement simulations. As a result, participants can manage their resources more intelligently, increase operational efficiency, and maximize business investment returns. This training emphasizes resource limitations, such as limited budgets and a lack of experience in financial planning. Moreover, the training focuses on the importance of financial management in business operations through simple transaction recording. In conclusion, this training helps new business owners run their businesses with effective financial management, establishing a solid foundation for achieving success in a competitive business world.